Nicotine Diminishes Alpha2-Adrenergic Receptor-Dependent Protection Against Oxidative Stress in H9c2 Cardiomyocytes - Del Calvo G; Pollard CM; Baggio Lopez T; Borges JI; Suster MS; Lymperopoulos A (Dove Medical Press, 2024)
Giselle Del Calvo, Celina M Pollard, Teresa Baggio Lopez, Jordana I Borges, Malka S Suster, Anastasios Lymperopoulos Laboratory for the Study of Neurohormonal Control of the Circulation, Department of Pharmaceutical Sciences (Pharmacology), Barry and Judy Silverman College of Pharmacy; Nova Southeastern University, Fort Lauderdale, FL, 33328, USACorrespondence: Anastasios Lymperopoulos, Pharmacology & Pharmaceutical Sciences, Department of Pharmaceutical Sciences, Barry and Judy Silverman College of Pharmacy, Nova Southeastern University, 3200 S. University Dr., HPD (Terry) Bldg./Room 1350, Fort Lauderdale, FL, 33328-2018, USA, Tel +1-954-262-1338, Fax +1-954-262-2278, Email al806@nova.eduIntroduction: Nicotine is a major component of cigarette smoke with various detrimental cardiovascular effects, including increased oxidative stress in the heart. Agonism of α2-adrenergic receptors (ARs), such as with dexmedetomidine, has been documented to exert cardioprotective effects against oxidative stress and related apoptosis and necroptosis. α2-ARs are membrane-residing G protein-coupled receptors (GPCRs) that primarily activate Gi/o proteins. They are also subjected to GPCR-kinase (GRK)-2-dependent desensitization, which entails phosphorylation of the agonist-activated receptor by GRK2 to induce its decoupling from G proteins, thus terminating α2AR-mediated G protein signaling.Objective: In the present study, we sought to examine the effects of nicotine on α2AR signaling and effects in H9c2 cardiomyocytes exposed to H2O2 to induce oxidative cellular damage.Methods and Results: As expected, treatment of H9c2 cardiomyocytes with H2O2 significantly decreased cell viability and increased oxidative stress, as assessed by reactive oxygen species (ROS)-associated fluorescence levels (DCF assay) and superoxide dismutase activity. Both H2O2 effects were partly rescued by α2AR activation with brimonidine in control cardiomyocytes but not in cells pretreated with nicotine for 24 hours, in which brimonidine was unable to reduce H2O2-induced cell death and oxidative stress. This was due to severe α2AR desensitization, manifested as very low Gi protein activation by brimonidine, and accompanied by GRK2 upregulation in nicotine-treated cardiomyocytes. Finally, pharmacological inhibition of adenylyl cyclase (AC) blocked H2O2-dependent oxidative damage in nicotine-pretreated H9c2 cardiomyocytes, indicating that α2AR activation protects against oxidative injury via its classic coupling to Gai-mediated AC inhibition.Discussion/Conclusions: Nicotine can negate the cardioprotective effects of α2AR agonists against oxidative injury, which may have important implications for patients treated with this class of drugs that are chronic tobacco smokers.Keywords: α2-adrenergic receptor, oxidative stress, cardiac myocyte, nicotine, GRK2, signal transduction, desensitization, α2-adrenergic agonist, adenylyl cyclase, superoxide dismutase